The Story of Yusuf in Genesis 39:11-23 and its Implications for the Attitude of Christian Youth in Facing Promiscuity - Kikhau, Resna Syarlina; Bahan, Jhilianti; Talan, Lidia; Y. Kake, Yada; Nenosaet, Febrianti; Seran, Neri J .R. (JUPE : Jurnal Pendidikan Mandala, 2025)
This article discusses the story of Joseph in Genesis 39:11-23 and relates it to the implications for the attitudes of today’s Christian youth in dealing with promiscuity. The aim of this research is. (1) what can be learned from Joseph's steadfastness in facing the temptations of Potiphar's wife (2) why did Joseph choose to respond to Potiphar's wife's offer by refusing, even though there were big risks he had to face. (3) how the suffering that Joseph experienced while he was told can be a love for young Christians in facing the consequences of the right decision.facing the consequences of the right decision The result of this research is that Yusuf's leadership can be a model as a good lesson not only for individuals in leadership positions but for all those who want to improve their character.